Pengaruh Social Media Marketing dan Brand Image Terhadap Minat Beli Produk Lemonilo Mi Instan - Nurul Arofah, Tria; Setiyarini, Triana (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the effect of social media marketing and brand image on the purchase intention of Lemonilo Instant Noodles. The research method used is quantitative with a population of students from the Faculty of Economics, Trunojoyo University Madura who have seen Lemonilo advertisements on social media. A total of 100 respondents were selected using purposive sampling, while data analysis was conducted using Partial Least Square Structural Equation Modeling (PLS-SEM). The results show that social media marketing has a positive and significant effect on purchase interest, indicating that creative and interactive digital communication strategies can attract attention and build closeness with consumers. In addition, brand image also has a positive and significant effect on purchase intention, confirming that a strong brand image as a healthy product can increase consumer trust and preference. Thus, this study confirms that optimizing social media marketing and strengthening brand image are important factors in increasing purchase intention and Lemonilo's competitiveness in the instant noodle industry.